2000
DOI: 10.1038/sj.bjp.0703516
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine‐1‐phosphate reduces rat renal and mesenteric blood flow in vivo in a pertussis toxin‐sensitive manner

Abstract: 1 Sphingolipids such as sphingosine-1-phosphate (SPP) and sphingosylphosphorylcholine constrict isolated rat intrarenal and mesenteric microvessels in vitro. The present study investigates their e ects on the cardiovascular system in vivo in anaesthetized rats. 2 The animals were given intravenous or intrarenal arterial bolus injections of sphingolipids (0.1 ± 100 mg kg 71 ) with subsequent measurements of mean arterial pressure, heart rate and renal and mesenteric blood¯ows (RBF, MBF) using a pressure transdu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
70
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(71 citation statements)
references
References 24 publications
(41 reference statements)
1
70
0
Order By: Relevance
“…To further support our in vitro findings, we performed an in vivo study by measuring RBF responses to bolus injections of S1P in anesthetized rats. Consistent with the report by Bischoff et al, 15 intravenous injection of exogenous S1P decreased RBF without significant changes in BP. The rapid reduction and recovery in RBF in response to a bolus of S1P are consistent with the behavior of S1P on afferent arteriolar reactivity measured in the in vitro.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…To further support our in vitro findings, we performed an in vivo study by measuring RBF responses to bolus injections of S1P in anesthetized rats. Consistent with the report by Bischoff et al, 15 intravenous injection of exogenous S1P decreased RBF without significant changes in BP. The rapid reduction and recovery in RBF in response to a bolus of S1P are consistent with the behavior of S1P on afferent arteriolar reactivity measured in the in vitro.…”
Section: Discussionsupporting
confidence: 82%
“…1,2,5 Recent studies indicate that S1P plays an important role in regulating vascular tone in resistance vessels, including cerebral, coronary, and mesenteric arteries 16,[27][28][29][30][31][32] ; however, very little is known about the renal influence of S1P under either physiologic or pathophysiologic conditions. Bischoff et al reported that S1P vasoconstricted isolated intrarenal arteries 14 and reduced RBF without changing arterial pressure in anesthetized rats, 15 indicating that S1P may be an important regulator of renal vascular function. The intrarenal arteries, however, contribute less to overall renal vascular resistance than microvessels and the S1P receptor signaling pathways involved in S1P-mediated renal vasoconstriction are also unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, our results suggest that the mechanism by which this facilitatory response occurs is associated with change of S1P 3 expression during culture. S1P caused slight vasoconstriction in rat renal and mesenteric micro-vessels (26). In addition, S1P did not induce any contractile response in coronary, femoral, and carotid arteries isolated from rats (21).…”
Section: Discussionmentioning
confidence: 94%
“…S1P receptor expression has been documented in endothelial as well as in vascular smooth muscle cells 19,23 . Bischoff et al 24,25 indeed reported that S1P constricted renal and mesenteric microvessels in vitro and reduced renal and mesenteric blood flow in vivo. As yet, however, there is no study to explore the expression and role of S1P expression in the cerebral vasospasm after SAH.…”
Section: Introductionmentioning
confidence: 99%